Bacterial community responses to the redox profile changes of mariculture sediment. (May 2021) - Shi, Rongjun; Han, Tingting; Xu, Shumin; Huang, Honghui; Qi, Zhanhui; Zhu, Qingzhi
Abstract: Suspended mariculture has significantly influences on the benthic sediment. However, our understanding on how bacterial communities respond to mariculture induced changes in redox profiles is limited. In present study, sediments from two maricultures and reference areas were collected and incubated for 28 day. The results indicated that the dominant pathway of organic matter mineralization in the sediment varied from groups, in the reference, it was the iron reduction, but in the two mariculture groups it was the SO4 2− reduction. Remarkable changes of bacteria community were recorded in the aerobic zone, where the abundances of 14 OTUs belonging to Gammaproteobacteria and Alphaproteobacteria were significantly higher than that in oxidation and anaerobic zones. However, 4 keystone OTUs were strictly anaerobic and belonging to Desulfobacteraceae ( n = 3) and Marinilabiaceae ( n = 1). The main environmental drivers determining sediment bacterial distribution were the particle organic carbon, dissolve oxygen, NO3 −, and moisture content. Graphical abstract: Unlabelled Image Highlights: Redox profiles of sediments from no-culture and mariculture groups were different. The dominant organic carbon mineralization path was SO4 2− reduction in mariculture sediment. Great changes of sediment bacteria in aerobic zones of mariculture were observed. Four keystone OTUs belonged to Deltaproteobacteria and Bacteroidetes. POC, DO, NO3 −, moisture played crucial roles in shaping bacterial distribution.